Distribución de las Funciones Retóricas de las Citas en los Apartados del Trabajo Fin de Máster Escrito en Español y en Inglés - Sánchez-Jiménez, David (HERMES - Journal of Language and Communication in Business, 2021)
This study correlates with a research study published in the journal Pragmalingüística, in which the contrastive use of the rhetorical functions of citations in master’s theses in Spanish and English was studied. The main objective pursued by this new research is to determine which rhetorical functions are used most frequently in the different parts of a master’s thesis and what these can accomplish in each part of the text. Following Petrić (2007), a computerized textual analysis of the rhetorical function of citation was used to study this phenomenon in a corpus of sixteen (16) theses of which eight (8) were written by American and eight (8) by Spanish postgraduates in their native language. With regards to cultural conventions, the results showed that when compared to native Spanish writers, the Americans students use the highest number of citations and write a relatively longer Introduction and Conclusion parts. The sets of functions are consonant with the rhetorical purpose of each part, which thus shows a close link between the citation and the structural organization of the academic text, despite the frequent use of Attribution (AT) in most parts of the thesis.